Study on the method of measuring the interface of radioactive liquid by air blowing - Fengna Tang; Jianwei Liu; Daoliang Chen (International Journal of Advanced Nuclear Reactor Design and Technology, 2025)
Aiming at the interfacial measurement method of radioactive liquids, we propose and validate a program to realize the interfacial measurement of radioactive liquids by using the air blowing method. Firstly, the measurement principle of the air blowing method is described; secondly, based on the traditional air blowing measurement method, multi-parameter cooperative operation and adaptive density compensation algorithm are added to design the interface measurement system of the air blowing method, and the computational logic of the interface measurement is theoretically deduced; thirdly, the validation test of the interface measurement is carried out; lastly, the results of the test are analyzed to illustrate the validity of the interface measurement method proposed in this paper.